Transcatheter arterial chemoembolization for lung malignant tumors - Zhang, Fenxiang; Liu, Yujin (Frontiers in Oncology, 2025)
Transcatheter arterial chemoembolization may enhance the local concentration and cytotoxicity of chemotherapeutic drugs and block the blood supply to the tumor, with an expectation to control the tumor, relieve hemoptysis, and prolong survival. This review will introduce the research progression of blood supply to lung cancer, discuss pulmonary artery chemoembolization (PACE) and bronchial artery chemoembolization (BACE) for lung cancer, including their indications and contraindications, operation techniques, efficacy assessments, combined treatments as well as their operating complications and the methods to prevent the adverse event. We will discuss the problems and challenges of percutaneous vascular intervention for lung cancer, such as the uncertainty of blood supply artery for lung cancer, the necessity of high-quality controlled studies, and the best choice for the indications. We hope to explore the direction of transcatheter arterial chemoembolization for lung cancer. The aim of this review is to provide a reference for the practice of chemoembolization by vascular interventional radiology for lung cancer.